1993
DOI: 10.2527/1993.713557x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of source and amount of dietary protein on performance, blood metabolites, and reproductive function of primiparous beef cows2

Abstract: Forty Angus x Hereford 2-yr-old primiparous cows (358 kg) were used to determine the effects of source and amount of CP on performance, reproductive function, and metabolic status of suckled primiparous cows. A 2 x 2 factorial treatment arrangement was used; cows received either 100 or 150% of NRC recommendations for CP in diets that contained either soybean meal (low escape = L) or corn gluten meal/blood meal (high escape = H) as the principal supplemental protein source. Resulting treatments were 100-L, 100-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
47
6
2

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 33 publications
7
47
6
2
Order By: Relevance
“…The effect of supplemental protein for beef cows has mostly been examined in cows fed basal diets containing considerably less CP than in our trials (De Gracia and Ward 1991;Rusche et al 1993;Triplett et al 1995). In our trials protein intake from silage alone was at least 20% in excess of NRC (1996) requirements; therefore, a response to protein should not have been observed for any level of supplementation.…”
Section: Effect Of Protein Level On the Response To Proteinmentioning
confidence: 99%
See 4 more Smart Citations
“…The effect of supplemental protein for beef cows has mostly been examined in cows fed basal diets containing considerably less CP than in our trials (De Gracia and Ward 1991;Rusche et al 1993;Triplett et al 1995). In our trials protein intake from silage alone was at least 20% in excess of NRC (1996) requirements; therefore, a response to protein should not have been observed for any level of supplementation.…”
Section: Effect Of Protein Level On the Response To Proteinmentioning
confidence: 99%
“…This suggested that the response by cows was from the UIP, rather than from the overall increase in CP concentration. Other research has also shown responses to UIP supply up to a certain level (Blasi et al 1991;De Gracia and Ward 1991;Rusche et al 1993;Triplett et al 1995). On silage-based diets, this can be attributed to low metabolizable protein supply, possibly due to a highly degradable protein source combined with a lack of energy available to rumen microbes for microbial protein synthesis (AFRC 1990).…”
Section: Effect Of Protein Source On the Response To Proteinmentioning
confidence: 99%
See 3 more Smart Citations